IDENTIFICATION OF PENTAGAMAVUNON-0 METABOLITE IN FAECES AFTER INTRAVENOUS INJECTION OF WHITE-MALE SPRAGUE DAWLEY-DERIVED RATS - Hadi, Feriyanto Trisna; ., Sugiyanto; ., Oetari (INDONESIAN JOURNAL OF PHARMACY, 2001)
The compound 2,5-bis-(4â-hydroxy-3â-methoxybenzilidin) cyclopentanone or Pentagamavunon-0 (PGV-0) as the new anti-inflamatory drug candidate, is one of curcumin structure modification. Identification of metabolites in faeces could be strengthen the whole information about biotransformation of drug and could be use for studying on PGV-0 metabolites which are excreted through bile. Male Sprague Dawley derived rats were used in all experiments. PGV-0 was given intravenously using dose at 40 mg/kg BB. Then the faeces callected after 24 and 48 hours. The metabolite investigation devided into two parts, etil acetate fraction and water fraction, of faeces. The faeces which is excreted after 24 hours, found was more-polar metabolite according to PGV-0; it has shoft-yellow flourencese and having Rf value = 0,48 on TLC, using silica gel F254 as the stationary phase and etil acetate as the mobile phase. No PGV-0 glucuronide and sulfate metabolites were detectable in faeces, which are excreted on 24 or 48 hours.Key words : Pentagamavunon-0, biotransformation, intravenous, faeces